Auld lang syne [videorecording (DVD)] - Carr-Wiggin, Joan; Kash, Linda, 1967-; Kuzyk, Mimi; Allen, Ryan (Gravitas Ventures, 2024)
Two broke, out-of-work actresses in their sixties hide out on a luxurious film set so they can have their dream Christmas. When a young security guard discovers them, they pretend to be the successes they never were.